Lack of evidence for a reciprocal interaction between bacterial and cytomegalovirus infection in the allogeneic stem cell transplantation setting - Vinuesa, Víctor; Solano, Carlos; Giménez, Estela; Piñana, José L.; Boluda, Juan Carlos Hernández; Amat, Paula; Navarro, David (Transplant international, 2016)
Summary Pathogenic interactions between bacteria and cytomegalovirus (CMV) may potentially occur early after allogeneic stem cell transplantation (allo‐SCT). This possibility nevertheless has not been investigated in depth. This was a retrospective study that included 170 consecutive patients who underwent 173 allo‐SCTs. Both bacterial infection (most of which were bacteremic) and CMV DNAemia were detected in 78 allo‐SCTs (62.9%). In total, 51 and 32 episodes of bacterial infection preceded or occurred after CMV DNAemia detection, respectively. Both events were diagnosed concurrently in four allo‐SCTs. The cumulative incidence of bacterial infection (of any type) over the study period was comparable in patients with or without a preceding episode of CMV DNAemia (P = 0.321). Cox proportional hazards regression analysis failed to identify CMV DNAemia as a significant risk factor for bacterial infection. Likewise, the cumulative incidence of CMV DNAemia within the study period was not significantly different in patients with or without a preceding episode of bacterial infection (P = 0.189). Furthermore, the occurrence of bacterial infection within episodes of active CMV infection had no apparent impact on the kinetics of CMV DNAemia. Our data, thus, do not support the existence of a bidirectional synergistic effect between bacterial infection and active CMV infection in the allo‐SCT setting.